1998
DOI: 10.2116/analsci.14.389
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Analysis of High-Level Radioactive Waste Glass by ICP-AES

Abstract: In a reprocessing plant for spent nuclear reactor fuel, the spent fuel is dissolved in concentrated nitric acid solution, and plutonium and unburned uranium are removed in the chemical separation process. The remaining solution contains more than 99% of the nonvolatile fission product elements, impurities from the cladding materials, corrosion products, traces of unseparated plutonium and most of the transuranic elements. This reprocessing waste is called high-level radioactive liquid waste (HLLW). The HLLW is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…A variety of alkaline fusion methods exist for a complete dissolution of, e.g., geological, environmental and nuclear decommissioning samples. These methods utilise sodium hydroxide [6,7], lithium borate [8,9], sodium peroxide [10,11] and similar alkaline compounds in different mixtures together with high temperature (most often over 600 °C) for complete destruction of even resistant silica minerals. In traditional methods, alkaline fusion is carried out in crucibles which are manually placed in and out of the oven.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of alkaline fusion methods exist for a complete dissolution of, e.g., geological, environmental and nuclear decommissioning samples. These methods utilise sodium hydroxide [6,7], lithium borate [8,9], sodium peroxide [10,11] and similar alkaline compounds in different mixtures together with high temperature (most often over 600 °C) for complete destruction of even resistant silica minerals. In traditional methods, alkaline fusion is carried out in crucibles which are manually placed in and out of the oven.…”
Section: Introductionmentioning
confidence: 99%
“…but these methods require laborious sample preparation and cannot be used outside the laboratory for eld applications. 4 The major advantage of LIBS lies in its ability to perform elemental analysis of any type (dielectrics, metals, etc.) or state (solids, liquid and gas) of samples.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, ICP-AES has been widely selected as the technique of choice to perform the analysis of metallic constituents owing to its simultaneous measurement capability, wide dynamic analytical range, high sensitivity and relative freedom from matrix interferences [3,4]. A number of studies have been reported on the application of ICP-AES to the determination of the trace or minor metal constituents in nuclear materials such as uranium, plutonium, oxides/carbides of uranium and plutonium, high-level radioactive waste glass and simulated nuclear waste solutions after the prior chemical separation of the major matrix [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%